Conceptualising entrepreneurship in a transition context. (6th February 2006) - Smallbone, David; Welter, Friederike
The paper sets out to review entrepreneurship in transition countries, assessing the extent to which theories and concepts of entrepreneurship developed in a market economy context can provide an appropriate interpretative framework. This is done in order to develop propositions for a model of entrepreneurship under transition conditions, which captures (1) the distinctive features of entrepreneurship, (2) the context for entrepreneurship in these countries and (3) the entrepreneurial process. The paper builds on previous papers by the authors, selectively using empirical evidence to support appropriate conceptualisation.